Territorialidade, saúde e meio ambiente : conexões, saberes e práticas em comunidades quilombolas de Sergipe - Lacerda, Roberto dos Santos (2017)
The quilombola communities do not solely exist as spatial groupings of former fugitive enslaved people, but have actually constituted themselves over the course of time as territories of resistance and preservation of the values, knowledge, and practices of afro-brazilian culture. In addition to a cosmovision that is inclusive, holistic, and integral, the emphasis on providing care for people and for the natural environment were crucial determining factors for the physical and cultural survival of the afro descendent populations. Their continued resistance to the slavocratic social system and to racism, a structuring element in brazilian society that persists until today, is underwritten by the communities’ core values. As soon as we begin to discuss health and quilombola territories, the two appear to be intimately tied. We see that the construction of the territory produces identities and that identities also produce territories, this process being a product of collective and reciprocal actions of social subjects. The ecosystemic focus on human health presents an opportunity to construct a theory-practice in navigating the relationships between health and the environment including, among other factors, an examination of the lifestyles of specific population groups. The objective of this particular study is to analyze how traditional wisdom and practices in quilombola health and healing construct territorialities that contribute to environmental conservation in their communities. Based on the Ethnographic method, with a qualitative approach and data analysis from Symbolic Interactionism, this study realized a field study at the quilombola communities Mocambo, Porto da Folho, and in Sítio Alto, in Simão Dias, both in Sergipe. Participant observation, interviews, iconographic registries, and a field study journal were all used as techniques for data collection. Among the wisdoms and practices observed articulating both health and the environment, we paid special attention to the use of medicinal plants, practices of prayers and blessings, the conservation of creole seeds (“sementes crioulas”), and the circular dances of samba de côco and danza de roda. We identify territoriality of resistance, territoriality of care, and territoriality of hope as common threads that link the two communities’ knowledge systems and practices relating to health and the environment. We conclude that the focus on the environment when examining the health of the quilombola communities illustrates a vital and integrative dynamic that intimately links health with the natural environment. The strategies, values, and practices that we found work to integrate the territory, health, and environment in the communities that we observed. As such, it is important to recognize and valorize the diversity of the conceptions and knowledge systems that promote unity and respect between human relations and the natural environment.________________________________________________________________________________________________________________________________